Thermal conductivity of nanofluids: A comparison of EMD and NEMD calculations. (December 2019) - Fujiwara, K.; Daimo, M.; Ueki, Y.; Ohara, T.; Shibahara, M.
Highlights: Effective thermal conductivity (ETC) of nanofluids was investigated by MD. Components of ETC were compared by EMD and NEMD calculations. Component of solid-solid interaction in a nanoparticle affected change of ETC. EMD and NEMD calculations showed good agreement for not only ETC but also components. Abstract: Extensive studies on the effective thermal conductivity (ETC) of nanofluids have been conducted thus far; however, the mechanisms behind the change in ETC remain unclear. In the present study, we investigated the components of the ETC of nanofluids, based on equilibrium molecular dynamics (EMD) and non-EMD (NEMD) calculations, to elucidate more accurately the mechanisms responsible for change in ETC. Until now, the factors affecting ETC have not been revealed clearly, and not compared quantitatively by the EMD and NEMD. This study also aimed to compare the constituents of ETC quantitatively to validate the NEMD calculation as a method for determining the ETC of nanofluids. Our detailed results demonstrate that the primary factors contributing to the change in ETC are thermal transport in liquid–liquid interactions and the solid–solid interactions in nanoparticles. The ETC components related to liquid exhibit consistency between the EMD and NEMD calculations, with less than 5.0% difference. Conversely, although the components related to nanoparticles result in differences of more than 10%, these properties do not appear to have a significant impact on ETC. On the basis of the findings of this study, we are able to calculate consistent results for not only ETC but also its components, via EMD and NEMD, for a liquid system with a spherical nanoparticle.